Jigsaw Type Cooperative Learning Model to Improve Student Learning Outcomes on Various Work Themes in Class IV State Primary School 064986 Medan Amplas - Nurul Annisa; Nurmaidina (International Journal of Educational Research Excellence (IJERE), 2023)
This study aims to determine the effectiveness of the Jigsaw cooperative learning model to improve student learning outcomes in thematic learning theme 4 "Various Jobs". This research was conducted in class IV SD Negeri 064986 Medan Sandpaper. This research is class action research (classroom action research). The subjects in this study were 17 grade IV students at SD Negeri 064986 Medan Amplas. Instruments and data collection techniques used in this study are observation and testing. From the observation results, it was found that only 5 students scored above the Minimum Completeness Criteria (KKM), and 12 students were below the KKM. The percentage of student learning outcomes only reached 29.91%. After taking action in cycle I, there was an increase in student learning outcomes. The percentage of student learning outcomes in the first cycle of the first meeting, namely 41.17%, and the percentage of student learning outcomes in the first cycle of the second meeting, namely 47.05% There was an increase in student learning outcomes by 17.63% in cycle I, from 29.41% at the time of observation to 47.05% at the end of cycle I. The percentage of student learning outcomes in cycle II at the first meeting, namely 64.70%, and the percentage of student learning outcomes in cycle II at the second meeting, namely 82.35%, There was an increase in student learning outcomes of 52.94% in cycle II, from 29.41% at the time of observation to 82.35% at the end of cycle II. Thus, it can be concluded that the use of the Jigsaw cooperative learning model can improve learning outcomes in theme 4, "Various Jobs," for fourth grade students at SD Negeri 064986 Medan Amplas.